Logistics integration in the supply chain: A resource dependence theory perspective - Sung-Tae Kim; Hong-Hee Lee; Taewon Hwang (International Journal of Quality Innovation, 2020)
Firms have strategically used cooperative linkages to establish competitiveness. In this study, we incorporated the resource dependency theory view to assess how trust, satisfaction, and commitment affect firms' decisions on logistics integration. Also, we examined the link between logistics integration and supply chain performance. The study collected data from 250 South Korean manufacturers for analysis. The results revealed positive impacts of trust, satisfaction, and commitment on logistics integration between manufacturing firms and logistics service providers that enhances logistics service capabilities of the firms. Furthermore, our study showed that building a strategic relationship for logistics services helps the manufacturing firms improve their business and operations performances in their supply chain. Implications and suggestions for future research are discussed.
Keywords: 650; Logistics integration; Supply chain performance; Trust; Satisfaction; Commitment